How To Communicate Islam Via New Media? Some Lessons From The Quraish Shihab Podcast - Adeni Adeni; Mudhofi Mudhofi (INJECT (Interdisciplinary Journal of Communication), 2022)
This article aims to answer how to communicate Islam through new media. Methodologically, this study is a ethnographic study that focuses on the Quraish Shihab Podcast channel. This study shows several findings; first, Islam must be communicated in a rational (logical) language. Second, Islamic communication must be considering the condition of the people being preached. Third, Islamic communication provides an alternative by providing various options and not forcing the message recipient. Fourth, communication via new media is substantive by basing each message on a deep understanding of the themes discussed. Fifth, Islamic communication must be humanistic, by prioritizing Islamic universal messages. These findings imply that the Islamic communication practices in the public space of new media must be able to create a peaceful space, encourage progress, strengthen culture and civilization, and facilitate good relations with others.